Anti-inflammatory effects of leaf and branch extracts of honeyberry (Lonicera caerulea) on lipopolysaccharide-stimulated RAW264.7 cells through ATF3 and Nrf2/HO-1 activation - An, Mi-Yun (Mol Med Rep, 2020)
Honeyberry (Lonicera caerulea) has long been used as a traditional medicine in China, Japan and northern Russia. Functional studies of honeyberry have mainly focused on the fruits, which have been reported to exert various pharmacological activities, including anti-inflammatory activity, with limited or no studies on the other parts of the plant, such as the leaves and branches. In the present study, the anti-inflammatory effects of extracts of the leaves (HBL), branches (HBB) and fruit (HBF) of honeyberry plant were evaluated in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. HBL and HBB significantly inhibited the production of pro-inflammatory mediators in LPS-stimulated RAW264.7 cells, and the inhibitory effects of HBL and HBB were stronger than those of HBF. HBL and HBB blocked the nuclear accumulation of p65 independently of IκB-α. HBL did not inhibit the phosphorylation of ERK1/2 or p38; however, HBB effectively inhibited the phosphorylation of p38 but not ERK1/2. HBL and HBB increased the expression of heme oxygenase-1 (HO-1) protein by inducing the nuclear accumulation of nuclear factor erythroid 2-related factor 2 (Nrf2) through the activation of the reactive oxygen species (ROS)/p38 pathway; the reduction in inducible nitric oxide synthase (iNOS) and interleukin-1β (IL-1β) expression by HBL and HBB was inhibited by HO-1 knockdown. In addition, HBL and HBB increased the expression of activating transcription factor-3 (ATF3), and the reduction in iNOS and IL-1β expression by HBL and HBB was inhibited by ATF3 knockdown. Collectively, HBL and HBB inhibited LPS-induced nuclear factor-κB activation by blocking the nuclear accumulation of p65, increasing HO-1 expression through activation of the ROS/p38/Nrf2 pathway, and increasing ATF3 expression. Furthermore, HBB inhibited LPS-induced p38 phosphorylation. These findings suggest that HBL and HBB may have great potential as natural products for the development of anti-inflammatory drugs.